The Plaque Microbiota Community of Giant Panda (Ailuropoda melanoleuca) Cubs With Dental Caries - Ma, Rui; Hou, Rong; Guo, Jun-Liang; Zhang, Xiu-Yue; Cao, San-Jie; Huang, Xiao-Bo; Wu, Rui; Wen, Yi-Ping; Zhao, Qin; Du, Sen-Yan; Lin, Ju-Chun; Bai, Yu; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Dental caries severely hinders efficient access to adequate energy in wildlife. Different food supplies will develop characteristic plaque, and the microorganisms of these plaque are closely related to dental health. Here, plaque samples from panda cubs with caries and caries-free were collected for 16S rRNA high-throughput sequencing. All sequences clustered into 337 operational taxonomic units (OTUs; 97% identity), representing 268 independent species belonging to 189 genera, 98 families, 51 orders, 24 classes, and 13 phyla. Two groups shared 218 OTUs, indicating the presence of a core plaque microbiome. α diversity analysis showed that the microbial diversity in plaques with caries exceeded that of caries-free. The dominant phyla of plaque microbiota included Proteobacteria, Bacteroidetes, Firmicutes, Fusobacteria, and Actinobacteria. The dominant genera included unclassified Neisseriaceae, Actinobacillus, Lautropia, Neisseria, Porhyromonas, unclassified Pasteurellaceae, Moraxella, Streptococcus, Bergeywlla and Capnocytophaga. β diversity analysis showed that the plaque microbial community structure was different between two groups. Using LEfSe analysis, 19 differentially abundant taxa were identified as potential biomarkers. Finally, function predictions analysis showed All the energy related metabolic pathways on KEGG level 2 were enriched in caries-active group. Consistent with the mainstream caries-causing narrative, our results illuminate the lack of information regarding the oral microflora composition and function within giant panda cubs.